What Will We Do? The Action Plan From a Brazilian Professional Football Club Youth Academy Facing the COVID-19 Pandemic - Morbi, Murilo dos Reis; Kopanakis, Annie Rangel; Mateu, Pau; Graeff, Billy; Marques, Renato Francisco Rodrigues (Frontiers in Sports and Active Living, 2021)
In 2020, the world was affected by the COVID-19 pandemic, which remains a major challenge for most countries today. In Brazil, football clubs' youth academies have faced a disruption of their regular activities. In order to study how the learning cultures of a Brazilian professional football club youth academy have been changed, and the alternatives created by the club's staff within this context, this perspective article aims to analyze how they have structured the Under-15 (U15) team learning culture during social isolation due to the COVID-19 pandemic. Through document and thematic analysis on a Brazilian professional football club's youth academy program, we promoted a dialogue between the process of adaptation to remote theoretical-tactical teaching with the learning theory proposed by Hodkinson and collaborators. The main theme of analysis of this study was the remote structure of the theoretical-tactical learning and physical training. Challenged with the need to transpose face-to-face activities into a learning culture based on remote communication, the U15 team coaching staff created a process to prescribe physical training, and to teach and discuss football tactical issues with young players during the period of social isolation. This perspective article shows that it is possible for sports institutions to create programs for the development of young athletes within the social isolation/distancing context, considering both theoretical-tactical learning and physical training processes. The adaptation to remote environments as structures for the learning culture seems a challenge, but is also a good alternative for young players to develop their interpretation and perception of football theoretical-tactical issues.